2007
DOI: 10.1007/s10995-007-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study: Knowledge about the Benefits of Breastfeeding and Barriers for Initiation in Mothers of Children with Spina Bifida

Abstract: The aim of the study is to identify the level of knowledge on breastfeeding by mothers of infants with spina bifida and the barriers encountered in initiating breastfeeding. A non-probabilisitic sample (n=30) of mothers was used in this study. The sample was obtained in two institutions specializing in care for infants with congenital anomalies in Puerto Rico. A self-administered questionnaire was used consisting of six sections. Descriptive statistics were used for data analysis. Among participants, 56.7% had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Neonates with severe NAS may be separated from their mothers for close monitoring, scoring of withdrawal symptoms, and pharmacologic treatment in the NICU, which presents barriers to successful breastfeeding (Rivera, Torres, Rodríguez, de Longo, & Peralta, 2008). Lactation consultants who are familiar with the NAS symptoms that interfere with the infant's ability to latch-on and adequately nurse are essential for breastfeeding success (Farid et al, 2008;Jansson, 2011;Tilton, 2012).…”
Section: Rooming-inmentioning
confidence: 99%
“…Neonates with severe NAS may be separated from their mothers for close monitoring, scoring of withdrawal symptoms, and pharmacologic treatment in the NICU, which presents barriers to successful breastfeeding (Rivera, Torres, Rodríguez, de Longo, & Peralta, 2008). Lactation consultants who are familiar with the NAS symptoms that interfere with the infant's ability to latch-on and adequately nurse are essential for breastfeeding success (Farid et al, 2008;Jansson, 2011;Tilton, 2012).…”
Section: Rooming-inmentioning
confidence: 99%
“…Similarly, Torowicz et al 4 demonstrated how the high-stress environment of congenital heart defect patients complicates the establishment of a milk supply. Rivera et al 5 highlighted the role of the clinical environment, medical staff knowledge, and hospital routines in shaping breastfeeding experiences for infants with spina bifida.…”
Section: Introductionmentioning
confidence: 99%
“…However, childhood acute and chronic illness or disability is associated with increased challenge and lower breastfeeding rates [ 8 11 ]. Many of these sick children are cared for in the paediatric setting, which is a separate organisational directorate to the neonatal and maternity units.…”
Section: Introductionmentioning
confidence: 99%